Urinary Bladder Matrix Grafting: A Simple and Effective Alternative to Flap Coverage for Wounds in High-Risk Orthopaedic Trauma Patients. Issue 4 (April 2022) - Parry, Joshua A.; Shannon, Steven F.; Strage, Katya E.; Hadeed, Michael M.; Heare, Austin; Stacey, Stephen; Hammerberg, E. Mark; Mauffrey, Cyril
Summary: Complex traumatic and/or infected wounds and their sequelae are a significant burden for high-volume trauma centers. Local or free flap coverage options are well described; however, they may be high risk in poor hosts with multiple comorbidities and active infections. In addition, flap coverage can result in delays in wound coverage depending on specialist availability. Porcine urinary bladder matrix grafting has been shown to be a simple definitive wound coverage option that can be performed without delay in multiple patient populations for wounds that would otherwise require flap coverage. The purpose of this article was to describe a technique for urinary bladder matrix grafting and report on a series of orthopaedic trauma patients treated with this technique.